Funding Self-Management - Donald A. R. George (Queen's University, Department of Economics, 1992)
The paper briefly summarizes those arguments which explain the paucity of workers' cooperatives under capitalism in terms of their financing arrangements. The possibility is considered that a wage-earners' investment fund, of Scandinavian type, could act as an external funding agency for a 'cooperative sector' within a capitalist economy. A simple model is developed of such an economy with a fund in place. The dynamics of the model are analyzed and a number of simulation results reported. These results indicate the economic costs and consequences of various policies which such a fund might pursue.
Keywords: 330